Essential role for miR-196a in brown adipogenesis of white fat progenitor cells. - Masaki Mori (Public Library of Science (PLoS), 2012)
The recent discovery of functional brown adipocytes in adult humans illuminates the potential of these cells in the treatment of obesity and its associated diseases. In rodents, brown adipocyte-like cells are known to be recruited in white adipose tissue (WAT) by cold exposure or β-adrenergic stimulation, but the molecular machinery underlying this phenomenon is not fully understood. Here, we show that inducible brown adipogenesis is mediated by the microRNA miR-196a. We found that miR-196a suppresses the expression of the white-fat gene Hoxc8 post-transcriptionally during the brown adipogenesis of white fat progenitor cells. In mice, miR-196a is induced in the WAT-progenitor cells after cold exposure or β-adrenergic stimulation. The fat-specific forced expression of miR-196a in mice induces the recruitment of brown adipocyte-like cells in WAT. The miR-196a transgenic mice exhibit enhanced energy expenditure and resistance to obesity, indicating the induced brown adipocyte-like cells are metabolically functional. Mechanistically, Hoxc8 targets and represses C/EBPβ, a master switch of brown-fat gene program, in cooperation with histone deacetylase 3 (HDAC3) through the C/EBPβ 3' regulatory sequence. Thus, miR-196a induces functional brown adipocytes in WAT through the suppression of Hoxc8, which functions as a gatekeeper of the inducible brown adipogenesis. The miR-196a-Hoxc8-C/EBPβ signaling pathway may be a therapeutic target for inducing brown adipogenesis to combat obesity and type 2 diabetes.